Association between Household Size and Family Functioning of Selected Families in Barangay 668, Ermita, Manila Using the APGAR Test Scores of the Mothers (2013) - 4 0 16; 5
Overpopulation has been stated as one of the main reasons for poverty in the Philippines. For this reason, overpopulation has been the target of many health programs which aims to control and decrease family size. These programs, however, have not been hugely successful. The results of the study would mainly benefit developers of health programs specially those advocating for family planning in that they would have better understanding and insight regarding family functions in association with variation in family sizes. A five-item questionnaire, the Family APGAR Scale was used to evaluate family functioning. The APGAR scale has five components for measuring family functioning: Adaptation, Partnership, Growth, Affection and Resolve. The mother was chosen to be the family representative to answer the questionnaire. A total of forty-six mothers from the chosen barangay participated in the study. The results of the study showed that a household of more than 5 members were 0.63 times less likely to have a dysfunctional family. This implies that bigger families are able to acknowledge and confront their own problems better than smaller families. The researchers suggest that future studies utilize larger sample populations to be able to better analyse the different factors affecting family functioning.
Keywords: 2 -- 0; 6; 20; 20; 2